Biomarkers in sarcoidosis. (1st November 2016) - Chopra, Amit; Kalkanis, Alexandros; Judson, Marc A.
ABSTRACT: Introduction : Numerous biomarkers have been evaluated for the diagnosis, assessment of disease activity, prognosis, and response to treatment in sarcoidosis. In this report, we discuss the clinical and research utility of several biomarkers used to evaluate sarcoidosis. Areas covered : The sarcoidosis biomarkers discussed include serologic tests, imaging studies, identification of inflammatory cells and genetic analyses. Literature was obtained from medical databases including PubMed and Web of Science. Expert commentary : Most of the biomarkers examined in sarcoidosis are not adequately specific or sensitive to be used in isolation to make clinical decisions. However, several sarcoidosis biomarkers have an important role in the clinical management of sarcoidosis when they are coupled with clinical data including the results of other biomarkers.